Prenatal Diagnosis of a Neurenteric Cyst by Magnetic Resonance Imaging - Gulrajani, Meenakshi; David, Karen; Sy, Wilfredo; Braithwaite, Angelica (American Journal of Perinatology, 1993)
We report a case of neuroenteric cysts in which the diagnosis was made prenatally by magnetic resonance imaging. These neuroenteric cysts are developmental anomalies of the alimentary tract in connection with midline neural structures that are usually diagnosed in the first decade of life. Magnetic resonance imaging not only helped to make the diagnosis early, but enabled appropriate counseling of the mother and follow-up of the infant so that planning of surgery was optimal.